The Burden of Atopic Dermatitis: Summary of a Report for the National Eczema Association - Drucker, Aaron M.; Wang, Annie R.; Li, Wen-Qing; Sevetson, Erika; Block, Julie K.; Qureshi, Abrar A. (Journal of investigative dermatology, 2017)
To assess the patient-level and societal burden of atopic dermatitis, we comprehensively reviewed the literature related to quality of life, social, economic, academic, and occupational impacts. Atopic dermatitis has profound impacts on patient and family quality of life. A conservative estimate of the annual costs of atopic dermatitis in the United States is $5.297 billion (in 2015 USD). People with atopic dermatitis may change their occupation because of their skin disease. Research gaps include quality of life assessments outside of tertiary care centers, impacts on partners and families of adult patients, and updated comprehensive cost estimates.